2015
DOI: 10.1002/adfm.201503889
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Thermometry on Silicon Surfaces Functionalized by Lanthanide‐Doped Self‐Assembled Polymer Monolayers

Abstract: The thermal gradients generated at submicrometer scale by the millions of transistors contained in integrated circuits are becoming the key limiting factor for device integration in micro‐ and nanoelectronics. Noncontact thermometric techniques with high‐spatial resolution are, thus, essential for noninvasive off‐chip characterization and heat management on Si surfaces. Here, the first ratiometric luminescent molecular thermometer implemented in a self‐assembled polymer monolayer functionalized Si surface is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…Recent examples on Tb 3+ /Eu 3+ ‐doped systems not discussed in this review and deserving remark are the works of Piñol et al, Brites et al, Rodrigues et al, and Ramalho et al (Table ) . The first two examples are discussed in more detail in Section .…”
Section: Luminescent Thermometers Based On Ln3+ Ionsmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent examples on Tb 3+ /Eu 3+ ‐doped systems not discussed in this review and deserving remark are the works of Piñol et al, Brites et al, Rodrigues et al, and Ramalho et al (Table ) . The first two examples are discussed in more detail in Section .…”
Section: Luminescent Thermometers Based On Ln3+ Ionsmentioning
confidence: 93%
“…The first two examples are discussed in more detail in Section . Rodrigues et al reported the thermometric functionalization of a Si surface with Tb 3+ and Eu 3+ complexes leading to S m = 1.45% K −1 , δT = 0.3 K (at 323 K), and cycle–recycle reliability of 98.6%. The hysteresis of the luminescence of the material results in a dual‐sensitive temperature regime.…”
Section: Luminescent Thermometers Based On Ln3+ Ionsmentioning
confidence: 99%
“…As one of the basic physical parameters, temperature plays a crucial role in many physical, chemical, and physiological processes. Explorations on high‐performance thermometers that are noninvasive, contactless, and particularly able to work at the nanoscale, have recently emerged as a widely desired topic . Among the myriad of options, luminescence‐based measurements have attracted enormous attention because of the tunable excitation and/or emission wavelengths, lifetimes, and intensities.…”
Section: Methodsmentioning
confidence: 99%
“…The thermal gradients generated at submicrometer scale by the millions of transistors contained in integrated circuits are becoming the key limiting factor for device integration in micro-and nanoelectronics and, then, non-contact thermometric techniques with high-spatial resolution (such as luminescent thermometry) are essential for non-invasive off-chip characterization and heat management. [141] The diureasil films incorporating [Eu(btfa) 3 (MeOH)(bpeta)] and [Tb(btfa) 3 (MeOH)(bpeta)] complexes allowed temperature mapping in wired-board circuits and in a Mach-Zehnder interferometer using commercial detectors and excitation sources. [118,138,140] For instance, Figure 9 shows temperature profiles of a FR4 printed wiring board reconstructed from the emission spectra of the Eu 3+ /Tb 3+ -containing di-ureasil.…”
Section: Luminescent Thermometersmentioning
confidence: 99%